2000
DOI: 10.1055/s-0042-1748004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Mismatch Negativity in the Responses of Individual Listeners

Abstract: The mismatch negativity (MMN) was recorded from normal adults in three stimulus conditions: two contrast conditions and a control condition in which standard and deviant stimuli were identical. Averaged waveforms were analyzed by examiners blind to the evoking stimulus condition. Hit rates, a false alarm rate, and d values were determined based on the number of MMNs identified in each condition. Hit rates were low and the false alarm rate was relatively high, resulting in unacceptably small d values. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…On a related point, Mathew et al (2017) , found correspondence between behavioral electrode discrimination and objective auditory change complex responses in recently implanted CI users. However, several papers have also reported on MMN and behavioral results that fail to correspond ( Dalebout & Fox, 2000 ; Kurtzberg et al, 1995 ; Ortmann et al, 2017 ; Uwer & von Suchodoletz, 2000 ). Thus, significant MMN responses do not preclude poor behavioral performances, and likewise, nonsignificant MMN responses do not preclude good behavioral performances ( Bishop & Hardiman, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…On a related point, Mathew et al (2017) , found correspondence between behavioral electrode discrimination and objective auditory change complex responses in recently implanted CI users. However, several papers have also reported on MMN and behavioral results that fail to correspond ( Dalebout & Fox, 2000 ; Kurtzberg et al, 1995 ; Ortmann et al, 2017 ; Uwer & von Suchodoletz, 2000 ). Thus, significant MMN responses do not preclude poor behavioral performances, and likewise, nonsignificant MMN responses do not preclude good behavioral performances ( Bishop & Hardiman, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MMN is a rather robust component observable in virtually all human participants, but in some occasions it might fail to be detected even in healthy participants with intact sound discrimination [ 82 , 83 ]. We used a simple automatic procedure to identify those participants that did not show a detectable MMN.…”
Section: Methodsmentioning
confidence: 99%
“…The MMN is a rather robust component observable in virtually all human participants, but in some occasions it might fail to be detected even in healthy participants with intact sound discrimination [80,81]. We used a 10/61 simple automatic procedure to identify those participants that did not show a detectable MMN.…”
Section: Validation Of Individual Mmnmentioning
confidence: 99%